In vitro assessment of the accuracy of extraoral periapical radiography in root length determination - Nazeer, Muhammad Rizwan (Eur J Dent, 2016)
OBJECTIVE: To determine the accuracy of extra oral periapical radiography in obtaining root length by comparing it with the radiographs obtained from standard intraoral approach and extended distance intraoral approach. MATERIALS AND METHODS: It was an in vitro, comparative study conducted at the dental clinics of Aga Khan University Hospital. ERC exemption was obtained for this work, ref number 3407Sur-ERC-14. We included premolars and molars of a standard phantom head mounted with metal and radiopaque teeth. Radiation was exposed using three radiographic approaches: Standard intraoral, extended length intraoral and extraoral. Since, the unit of analysis was individual root, thus, we had a total of 24 images. The images were stored in VixWin software. The length of the roots was determined using the scale function of the measuring tool inbuilt in the software. Data were analyzed using SPSS version 19.0 and GraphPad software. Pearson correlation coefficient and Bland–Altman test was applied to determine whether the tooth length readings obtained from three different approaches were correlated. P = 0.05 was taken as statistically significant. RESULTS: The correlation between standard intraoral and extended intraoral was 0.97; the correlation between standard intraoral and extraoral method was 0.82 while the correlation between extended intraoral and extraoral was 0.76. The results of Bland–Altman test showed that the average discrepancy between these methods is not large enough to be considered as significant. CONCLUSIONS: It appears that the extraoral radiographic method can be used in root length determination in subjects where intraoral radiography is not possible.